Cerebellar fastigial nucleus: from anatomic construction to physiological functions. Issue 1 (December 2016) - Zhang, Xiao-Yang; Wang, Jian-Jun; Zhu, Jing-Ning
Abstract Fastigial nucleus (FN) is the phylogenetically oldest nucleus in the cerebellum, a classical subcortical motor coordinator. As one of the ultimate integration stations and outputs of the spinocerebellum, the FN holds a key position in the axial, proximal and ocular motor control by projecting to the medial descending systems and eye movement related nuclei. Furthermore, through topographic connections with extensive nonmotor systems, including visceral related nuclei in the brainstem, hypothalamus, as well as the limbic system, FN has also been implicated in regulation of various nonsomatic functions, such as feeding, cardiovascular and respiratory, defecation and micturition, immune, as well as emotional activities. In clinic, FN lesion or dysfunction results in motor deficits including spinocerebellar ataxias, and nonmotor symptoms. In this review, we summarize the cytoarchitecture, anatomic afferent and efferent connections, as well as the motor and nonmotor functions of the FN and the related diseases and disorders. We suggest that by bridging the motor and nonmotor systems, the cerebellar FN may help to integrate somatic motor and nonsomatic functions and consequently contribute to generate a coordinated response to internal and external environments.